1996
DOI: 10.1152/ajpheart.1996.271.2.h417
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II formation in dog heart is mediated by different pathways in vivo and in vitro

Abstract: Angiotensin-converting enzyme (ACE) inhibitors (I) have beneficial effects that are presumably mediated by decreased angiotensin II (ANG II) production. However, in vitro assays in human heart extracts have demonstrated that > 75% of ANG II-forming enzyme activity was not inhibited by captopril (Cap) and therefore did not appear to be related to ACE but was inhibited by chymostatin, suggesting that it was predominantly chymase-like activity. Previous work in our laboratory has demonstrated a similar relative c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 0 publications
2
28
0
Order By: Relevance
“…Danser and colleagues (113,139) suggest that urinary renin may be an alternative measure of an active RAS within the kidney. Quenched fluorescent substrates based on the ANG- (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) sequence are available to measure renin. Although this approach does not rely on the detection of ANG I or an exogenous source of angiotensinogen, the sensitivity and specificity of the peptide substrates are not comparable with angiotensinogen.…”
Section: Ras Protein Componentsmentioning
confidence: 99%
“…Danser and colleagues (113,139) suggest that urinary renin may be an alternative measure of an active RAS within the kidney. Quenched fluorescent substrates based on the ANG- (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) sequence are available to measure renin. Although this approach does not rely on the detection of ANG I or an exogenous source of angiotensinogen, the sensitivity and specificity of the peptide substrates are not comparable with angiotensinogen.…”
Section: Ras Protein Componentsmentioning
confidence: 99%
“…4,8 We hypothesized that because chymase is present in the interstitium, chymase-mediated Ang II formation catalyzed by chymase should be substantial in the ISF space of the dog heart in vivo. Thus, our intent was to reproduce our in vitro assay conditions established in heart tissue extracts by infusion of Ang I substrate alone and Ang I plus inhibitors into the ISF space of the dog heart in vivo.…”
Section: Protocolmentioning
confidence: 99%
“…We chose 15 mol/L Ang I as the initial dose to infuse into the microdialysis probes, which was 40-fold lower than the 600 mol/L Ang I dose used in our in vitro experiments. 4,8 Our choices for doses of captopril and chymostatin ISF infusions were also based on our in vitro studies. 4,8 For the in vivo experiments, we chose chymostatin 1 mmol/L and captopril 2.5 mmol/L, 10 and 25 times the in vitro doses of chymostatin and captopril, respectively.…”
Section: Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…In striking contrast, experiments in vivo with normal 5,6 or failing dog hearts 7,8 have demonstrated that most (Ͼ70%) of the Ang II formation can be inhibited by an ACE inhibitor, indicating that, under these conditions, the major Ang IIforming enzyme is ACE. Moreover, in normal human hearts, Zisman et al 9 have demonstrated that, in vivo, the major Ang II-forming enzyme is ACE, as 90% of the Ang II formation could be inhibited by an ACE inhibitor.…”
Section: See P 2555mentioning
confidence: 90%